Bazhenov formation anomalous section within the Uvat oil and gas bearing area - Dmitry A. Staroselets; Pavel V. Smirnov; Anatoly V. Trenkin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to bring undeveloped sediments of the Bazhenov horizon to development in areas that are well explored and have developed infrastructure. Objects. Anomalous section deposits of the Bazhenov Formation (J3-K1bn) of Western Siberia within the Uvat oil and gas bearing region. Aim. To ascertain the spread boundaries and structure parametrization of sediments of the Bazhenov formation anomalous section within the Uvat oil and gas bearing region through an integrated analysis of the core material study results, GIS and seismic data. Methods. Photomaterials of three core samples and the results of macro- and micro-description of rocks, measurement of natural radioactivity on the core by the spectrometric gamma-ray logging, palynological and microfaunistic studies. To clarify the structure of the Bazhenov formation, geophysical well surveys and 3D seismic data were used. The logging materials are represented by 154 wells and include the following methods: intrinsic polarisation, gamma ray logging, induction, neutron and lateral logs. Results. The authors have carried out the analysis of the Bazhenov formation sediments within the Uvat oil and gas bearing area. They carried out the lithological and petrographic analysis of the formation sediments in thin sections and determined the contribution of radioactive elements to the total natural radioactivity, according to which, in combination with GIS data, the Bazhenov formation was differentiated into rocks of mainly siliceous composition, siliceous-carbonate rocks, mudstones and sandy-silty mudstones. Biostratigraphic studies of samples of the Bazhenov formation were analyzed. The deposits of the Bazhenov formation are dated by the Titonian (Volga) Stage, part of which is represented by a mixed composition containing both the amorphous organic matter typical of the Bazhenov formation and the Valanginian or Valanginian-Goterivian palynoforms of good preservation. The authors clarified the boundary of the Bazhenov formation anomalous section in the Uvat oil and gas area: in comparison with the previously established contours of distribution, the eastern boundary shifted to the west, due to which the total area of the anomalous section reduced almost twofold; the contours of the north-eastern border of Bazhenov formation anomalous section were slightly revised and shifted to the south-west direction. The obtained data indicate that the Bazhenov formation anomalous section formation was caused by the introduction of Valanginian-Gotterivian deposits into the Tithonian-Berriasian deposits of protobagenite, which confirms the geomechanical model of the Bazhenov formation anomalous section formation.